Utrecht work engagement scale in Chile: measurement, reliability and validity - Juyumaya, Jesús E. (Estudios de Administración, 2019)
Work engagement is described according to dedication, vigor and absorption. The most widely-used measure of work engagement is the Utrecht Work Engagement Scale (UWES). The purpose of this research was to study the psychometric properties of the abbreviated version of this scale (UWES-9) in the Chilean labor context. A cross-sectional survey design was used for a convenience sample (n = 255). The survey used the UWES-9 scale (Schaufeli & Bakker, 2003), the psychological empowerment scale of Spreitzer (1995) and the generic job satisfaction scale (Macdonald & MacIntyre, 1997). The reliability index (alpha) was calculated, resulting in good internal consistency. The three dimensions of the scale were correlated to a large extent, so it was not necessary to eliminate determined items. With respect to construct validity, work engagement was correlated in the expected (positive) direction with psychological empowerment and job satisfaction. Managerial implications and challenges for future research are discussed.